Genetic mechanisms of knee osteoarthritis: a population based case–control study. Issue 10 (10th September 2004) - Jones, G; Ding, C; Scott, F; Cicuttini, F
Abstract : Objective: To compare subjects who had at least one parent with a total knee replacement for severe primary knee osteoarthritis with age and sex matched controls who had no family history of knee osteoarthritis Design: Population based case–control study of 188 matched pairs (mean age 45 years, range 26 to 60). Methods: Articular cartilage volume and bone size were determined at the patella and at the medial tibial and lateral tibial compartments by processing images acquired using T1 weighted, fat saturated magnetic resonance imaging. Radiographic osteoarthritis (ROA) was assessed from a standing semiflexed radiograph scored for joint space narrowing and osteophytosis. Knee pain was assessed by questionnaire. Height, weight, body mass index (BMI), lower limb muscle strength, and endurance fitness were measured by standard protocols. Results: Compared with the controls, index offspring had higher BMI (27.8 v 26.0 kg/m 2, p = 0.02), weaker lower limb muscles (127 v 135 kg, p = 0.006), more knee pain (47% v 22%, p<0.001), and greater medial tibial bone area (17.6 v 17.1 cm 2, p = 0.01). With the exception of BMI, these differences persisted in multivariate analysis. There was a non-significant trend to higher cartilage volume at tibial sites and increased ROA in the offspring in the total and subgroup analyses, but no difference in height and endurance fitness. Conclusions: BMI, muscle strength, knee pain, and medial tibial bone area, but not cartilage volume, appear to play a role in the genetic regulation and development of knee osteoarthritis.